Pengaruh Peran Kepemimpinan, Organizational Citizenship Behavior dan Hubungan Industrial Terhadap Kinerja Karyawan pada PT. Sankeikid Manutec Indonesia - Maudyna Fatana; Dadan Ahmad Fadili (Jurnal Ilmiah Wahana Pendidikan, 2021)
The Influence of the Role of Leadership, Organizational Citizenship Behavior and Industrial Relations on Employee Performance at PT. Sankeikid Manutec Indonesia. Thesis. Faculty of Economics, Singaperbanga University, Karawang.This study aims to examine and analyze the influence of the role of leadership, organizational citizenship behavior and industrial relations on employee performance at PT. Sankeikid Manutec Indonesia.This research was conducted using quantitative methods with descriptive and verification analysis, namely, collecting, presenting, analyzing and testing hypotheses, as well as making conclusions and conclusions. The sample in this study amounted to 130 using a non-probability sampling technique with the saturated sample method. The data analysis technique used is Likert scale analysis technique and path analysis. Based on the analysis that has been done this research proves that the leadership role in Sankeikid shows an average value of 448.1 with the Agree criteria which means it is good, Organizational citizenship behavior in Sankeikid shows an average value of 463.06 with the Agree criteria which means it is good, Industrial Relations at Sankeikid shows an average score of 522.3 with the Agree criteria which means it is good and the Employee Performance at Sankeikid gets an average result of 451 with the Agree criteria which means it is good.